2010
DOI: 10.1007/s10064-009-0255-5
|View full text |Cite
|
Sign up to set email alerts
|

Lineament mapping and its application in landslide hazard assessment: a review

Abstract: This paper presents an overview of the use of lineaments in landslide hazard mapping. The lineaments are normally derived either from aerial photographs or satellite imagery. The relative advantages and disadvantages of digital image processing and manual (visual) lineament interpretation are discussed. Most researchers prefer the manual technique, despite the fact it is more time-consuming and subjective, as it allows a higher degree of operator control. Ways of increasing objectivity in the interpretation ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(54 citation statements)
references
References 108 publications
0
45
0
4
Order By: Relevance
“…The identification of lineaments would be extremely difficult if it is depended only on fieldwork. Lineament mapping and analysis is, however, a significant part of neotectonic and structural geology studies since they can provide essential clues about late Quaternary tectonic deformation and environmental hazards (Panizza and Castaldini, 1987;Shake and McHone, 1987;Gabrielsen et al, 2002;Ramli et al, 2010;Koike, 2011a, 2011b;Saadi et al, 2011;Ali, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of lineaments would be extremely difficult if it is depended only on fieldwork. Lineament mapping and analysis is, however, a significant part of neotectonic and structural geology studies since they can provide essential clues about late Quaternary tectonic deformation and environmental hazards (Panizza and Castaldini, 1987;Shake and McHone, 1987;Gabrielsen et al, 2002;Ramli et al, 2010;Koike, 2011a, 2011b;Saadi et al, 2011;Ali, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated good results in mapping linear discontinuities from satellite images [23][24][25][26]. The automatic lineament extraction algorithm in Geomatica 2015 software, integrated in the LINE module, was used in this study.…”
Section: The Automatic Lineament Extraction Algorithmmentioning
confidence: 99%
“…Lineament mapping is an important part of structural geology and they reveal the architecture of the underlying rock basement (Ramli et al, 2010). Lineament extraction involve both manual visualization and automatic lineament extraction through softwares such us PCI GeoAnalyst, Geomatica, Canny algorithm (e.g.…”
Section: Utility Of Dip Of Multispectral Medium Resolution Data To Gementioning
confidence: 99%
“…For example, Qari et al, (2008) extracted the structural information from Landsat ETM+ band 8 using PCI GeoAnalyst software by applying edge detection and directional filtering followed by overlaying with ASTER band ratio 6/8, 4/8, 11/14 in RGB to create a geological map. Kocal et al, (2004) urbanization, extensive weathering and recent non-consolidated deposits may hinder the detection of lineaments thus the need for ground truthing or earlier satellite images (Ramli et al, 2010).…”
Section: Utility Of Dip Of Multispectral Medium Resolution Data To Gementioning
confidence: 99%